2022
DOI: 10.4269/ajtmh.21-0362
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Seeking and Access to Care for Pneumonia, Sepsis, Meningitis, and Malaria in Rural Gambia

Abstract: Children with acute infectious diseases may not present to health facilities, particularly in low-income countries. We investigated healthcare seeking using a cross-sectional community survey, health facility-based exit interviews, and interviews with customers of private pharmacies in 2014 in Upper River Region (URR) The Gambia, within the Basse Health & Demographic Surveillance System. We estimated access to care using surveillance data from 2008 to 2017 calculating disease incidence versus distance to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…Empirical studies of malaria 13,14 have shown that delay in seeking early and appropriate care was largely due to poor perception of the risk of a child’s vulnerability to the diseases by the caregivers. In other studies 15,16 , most caregivers who demonstrated acceptable health-seeking behaviour recognised the danger signs for severe forms of malaria, pneumonia, diarrhoea and meningitis. However, few studies 15,17 have investigated the caregivers’ perception to the risk of dual or multiple infections such as malaria and worms.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Empirical studies of malaria 13,14 have shown that delay in seeking early and appropriate care was largely due to poor perception of the risk of a child’s vulnerability to the diseases by the caregivers. In other studies 15,16 , most caregivers who demonstrated acceptable health-seeking behaviour recognised the danger signs for severe forms of malaria, pneumonia, diarrhoea and meningitis. However, few studies 15,17 have investigated the caregivers’ perception to the risk of dual or multiple infections such as malaria and worms.…”
Section: Introductionmentioning
confidence: 80%
“…In other studies 15,16 , most caregivers who demonstrated acceptable health-seeking behaviour recognised the danger signs for severe forms of malaria, pneumonia, diarrhoea and meningitis. However, few studies 15,17 have investigated the caregivers’ perception to the risk of dual or multiple infections such as malaria and worms. Understanding the importance of malaria-helminth coinfection and its influence on health-seeking behaviour from the caregivers’ perspectives is critical to the development and uptake of integrated approaches to prevention and treatment to the co-infection.…”
Section: Introductionmentioning
confidence: 80%
“…Empirical studies on malaria [13,14] have shown that delay in seeking early and appropriate care was largely due to poor perception about the risk of a child's vulnerability to the diseases by the caregivers. In other studies [15,16], most caregivers who demonstrated acceptable health-seeking behaviour recognised the danger signs for severe forms of malaria, pneumonia, diarrhoea and meningitis. However, very few studies [15,17] have investigated the caregivers' perception to the risk of dual or multiple infections such as malaria and helminths.…”
Section: Introductionmentioning
confidence: 85%
“…In other studies [15,16], most caregivers who demonstrated acceptable health-seeking behaviour recognised the danger signs for severe forms of malaria, pneumonia, diarrhoea and meningitis. However, very few studies [15,17] have investigated the caregivers' perception to the risk of dual or multiple infections such as malaria and helminths. Understanding the importance of malaria-helminth co-infection and its influence on health-seeking behaviour from the caregivers' perspectives is critical to the development and uptake of integrated approaches to prevention and treatment to the co-infection.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation